Building equal partnerships: The Student Engagement Associate scheme at the University of Nottingham - Obadare, Ololade; Kohli, Taapsi; Watts, Matthew; Lymath, Dean (International Journal for Students as Partners, 2022)
The Student Engagement Associate scheme at the University of Nottingham showcases the impact of student-staff partnerships for positive change. Through these partnerships, the scheme has managed to produce innovative projects that underpin the institution’s core principles and has fostered a sense of equality and community between its staff partners and students. In the academic year of 2019/20, twenty students from diverse backgrounds were employed as student engagement associates and involved in projects such as the Digital Conduct module, the Equality, Diversity, & Inclusion (EDI) booklet, and the development of Student Reviewers, a scheme supporting pedagogic innovation.